2009
DOI: 10.1590/s1516-89132009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Estimation models of variance components for farrowing interval in swine

Abstract: The main objective of this study was to evaluate the importance of including maternal genetic, common litter environmental and permanent environmental effects in estimation models of variance components for the farrowing interval trait in swine. Data consisting of 1,013 farrowing intervals of Dalland (C-40) sows recorded in two herds were analyzed. Variance components were obtained by the derivative-free restricted maximum likelihood method. Eight models were tested which contained the fixed effects(contempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
6
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
6
6
0
2
Order By: Relevance
“…The heritabilities for FI across breeds and connectedness groups were low (ranged from 0.01 to 0.03), and this agrees with the report from previous studies (Akanno et al, ; Cavalcante Neto et al, ). Serenius et al (), using repeatability models for Finnish Landrace and Large White populations, obtained calculated heritability that varied from 0.04 to 0.16 for FI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The heritabilities for FI across breeds and connectedness groups were low (ranged from 0.01 to 0.03), and this agrees with the report from previous studies (Akanno et al, ; Cavalcante Neto et al, ). Serenius et al (), using repeatability models for Finnish Landrace and Large White populations, obtained calculated heritability that varied from 0.04 to 0.16 for FI.…”
Section: Discussionsupporting
confidence: 91%
“…The estimated repeatability for litter traits were in agreement with previous studies (Chen et al, ; Crump et al, ) and the repeatability estimates for FI obtained were similar with the report of (Cavalcante Neto et al, ), who reported an estimates ranging from 0.05 to 0.07 in a Brazil pig population.…”
Section: Discussionsupporting
confidence: 91%
“…Knowledge of the influence of environmental and genetic factors on these traits is becoming increasingly important (Cavalcante-Neto et al, 2009a;Leite et al, 2011), considering the geographic dimensions of Brazil, with regions of different climates, not to mention deficient management, inadequate facilities, and animals that are not always of high breeding value (Pinheiro et al, 2000;Cavalcante-Neto et al, 2008a, 2009b.…”
Section: Introductionmentioning
confidence: 99%
“…Esse ambiente comum afeta o desempenho dos animais em toda a sua vida e é determinado, principalmente, pela matriz, através dos seus cuidados com a cria, sua produção de leite etc. (CAVALCANTE-NETO et al, 2009;TORRES FILHO et al, 2005).…”
Section: Os Valores De Aic E Bic Também Apontaram O Modelo 1 Como O Qunclassified
“…Atualmente, em suínos, diversos trabalhos têm utilizado o efeito comum-de-leitegada nos modelos para estimação de componentes de variância, inclusive em características que se manifestam tardiamente na vida da fêmea suína, como as reprodutivas (CAVALCANTE-NETO et al, 2008, 2009CHIMONYO et al, 2006;KAUFMANN et al, 2000;LUKOVIC et al, 2003LUKOVIC et al, , 2004LUKOVIC et al, , 2007.…”
Section: Os Valores De Aic E Bic Também Apontaram O Modelo 1 Como O Qunclassified